Easing the “second-shift” burden : grandparental childcare and the subjective wellbeing of working mothers in Singapore - Cheo, Rachel Ka Yang (Nanyang Technological University, 2020)
Childcare arrangements lie at the crux of issues parents have to work out when mothers wish to continue with work after childbirth. However, it is still common for working mothers to bear the brunt of both domestic and paid work. In the present study, I explored the role of grandparents as providers of childcare for their grandchildren in contemporary Singapore. Specifically, I leveraged on Hobfoll’s (1988) Conservation of Resources theory to propose that grandparents play a beneficial role for working mothers’ subjective wellbeing because they can offer childcare resources that enable working mothers to engage in respite activities. The socioeconomic status (SES) of working mothers was also examined for potential moderating effects. Findings show that: grandparental childcare had a significant and positive relationship with working mothers’ respite engagement (Hypothesis 1); working mothers’ respite engagement was found to significantly predict for their subjective life satisfaction (Hypothesis 2); grandparental childcare had a significant and positive relationship with the subjective life satisfaction of working mothers, indirectly via their respite engagement (Hypothesis 3); and SES was found to have a nonsignificant interaction with grandparental childcare in predicting for working mothers’ respite engagement (Hypothesis 4). The present findings have illuminated the value of grandparental childcare in navigating the demands from domestic and paid work. More importantly, they have shed light on how grandparental childcare can affect the subjective life satisfaction of working mothers only via their respite engagement, regardless of SES levels.